Heightened Innate Immune and Inflammatory Gene Expression in the Skin of Severe COVID-19 Cases - Fernandes IG; Ferreira FM; De Sousa ESA; Pietrobon AJ; Teixeira FME; Ramos YÁL; Yendo TM; Pereira NZ; Sotto MN; Duarte-Neto AN; Orfali RL; Aoki V; et al. (Journal of Inflammation Research)
Iara Grigoletto Fernandes,1 Frederico Moraes Ferreira,2 Emanuella Sarmento Alho De Sousa,1,3 Anna Julia Pietrobon,1 Franciane Mouradian Emidio Teixeira,1 Yasmim Álefe Leuzzi Ramos,1 Tatiana Mina Yendo,1 Natalli Zanete Pereira,1 Mirian Nacagami Sotto,4 Amaro Nunes Duarte-Neto,4 Raquel Leão Orfali,1 Valeria Aoki,1 Luiz Fernando Ferraz Da Silva,4 Alberto José da Silva Duarte,1 Maria Notomi Sato1 1Laboratory of Medical Investigation 56, Department of Dermatology, University of São Paulo Medical School, São Paulo, Brazil; 2Cellular, Genetic, and Molecular Nephrology Laboratory (LIM-29), University of São Paulo Medical School, São Paulo, Brazil; 3Department of Immunology, Institute of Biomedical Sciences, University of São Paulo, São Paulo, Brazil; 4Laboratory of Medical Investigation 50, Department of Pathology, University of São Paulo Medical School, São Paulo, BrazilCorrespondence: Maria Notomi Sato, Laboratory of Medical Investigation in Dermatology and Immunodeficiencies (LIM-56), Department of Dermatology, Faculdade de Medicina, Universidade de Sao Paulo, Sao Paulo, SP, 05403-000, Brazil, Tel +55 11 30617499, Email marisato@usp.brPurpose: Cutaneous manifestations of SARS-CoV-2 infection exhibit significant variability, yet the role of innate immune responses in the skin of COVID-19 patients remains poorly understood. In this study, we investigated the transcriptomic profile of skin samples from patients who succumbed to COVID-19.Patients and Methods: Skin autopsies from COVID-19 patients with post-mortem time of less than 20 hours were obtained from University of São Paulo Medical School Hospital and healthy skin samples, were submitted to RNA sequencing analysis. Validation of differentially expressed genes (DEGs) was performed by real-Time PCR.Results: Our analysis revealed markedly elevated expression of type I interferon (IFN)-inducible antiviral factors, antioxidant enzymes, and components of several cytokine-signaling pathways in COVID-19 skin samples compared to healthy controls. SARS-CoV-2 infection robustly induced numerous interferon-stimulated genes (ISGs), IFITs, IRF, S100 family with a notable enrichment of those associated with antiviral and inflammatory responses. Moreover, the presence of counter-regulatory factors such as SOCS3 and NFKBIA indicate the involvement of anti-inflammatory mechanisms in the skin. Furthermore, deconvolution data indicated increased presence of macrophages other nucleated cells in vessels in the skin of COVID-19 patients, highlighting the involvement of innate immune mechanisms.Conclusion: The results revealed cutaneous alterations in the expression of genes associated with innate immunity and inflammation factors. This suggests that, unlike tissues with viral tropism, the skin is enriched with antiviral factors to defend against SARS-CoV-2. This information could be useful for developing specific antiviral therapies.Keywords: COVID-19, SARS-CoV-2, skin, RNA-Seq, innate immunity